Clinical, paraclinical and serological findings in Susac syndrome: an international multicenter study - Jarius, Sven; Kleffner, Ilka Anna Elisabeth; Dörr, Jan-Markus; Sastre-Garriga, Jaume; Illes, Zsolt; Eggenberger, Eric; Chalk, Colin; Ringelstein, Marius; Aktaş, Orhan; Montalbán, Xavier; Fechner, Kai; Stöcker, Winfried; et al. (Journal of neuroinflammation, 2014)
Susac syndrome (SuS) is a rare disorder thought to be caused by autoimmune-mediated occlusions of microvessels in the brain, retina and inner ear leading to central nervous system (CNS) dysfunction, visual disturbances due to branch retinal artery occlusions (BRAO), and hearing deficits. Recently, a role for anti-endothelial cell antibodies (AECA) in SuS has been proposed.
Gesehen am 06.08.2020